Concurrently Preparing Front Emitter and Rear Passivating Contact via Continuous PECVD Deposition Plus One‐Step Annealing for High‐Efficiency Tunnel Oxide Passivating Contact Solar Cells. Issue 7 (12th February 2023) - Du, Haojiang; Liu, Zunke; Liu, Wei; Xiao, Mingjing; Lin, Na; Yang, Weiguang; Xia, Qingfeng; Liao, Mingdun; Yan, Baojie; Yang, Zhenhai; Zeng, Yuheng; Ye, Jichun
Abstract : Although tunnel oxide passivating contact (TOPCon) solar cells (SCs) have achieved great success in the photovoltaic (PV) industry, the ultrahigh temperature to prepare boron emitters prolongs the preparation processes and increases the thermal budget. Herein, a new method is presented for simultaneously preparing the front‐side boron emitters and the rear‐side TOPCon structures through continuous plasma enhanced chemical vapor deposition of the precursor layers followed by one‐step high‐temperature annealing. The front‐side boron emitters are fabricated using a stack of nano‐SiO x /B‐doped a‐Si:H layers as the boron source, which can avoid the formation of the stacking faults and lower the annealing temperature to match the rear‐side TOPCon fabrication processes. The rear‐side TOPCon structure, consisting of a plasma‐assisted N2 O oxidation (PANO) SiO x and a nitrogen‐doped a‐Si:H( n + ), is used to match the B diffusion temperature with high‐quality passivation. The precursor TOPCon cell without electrodes features excellent passivation with the highest implied open‐circuit voltage ( iV oc ) of 726 mV. As a result, the proof‐of‐concept TOPCon SCs exhibit a remarkable efficiency of 24.07%. This work proposes a flexible and elegant process to prepare high‐efficiency TOPCon devices, which shows great potential for application in the PV industry. Abstract : A flexible method is demonstrated by using the continuous plasma enhanced chemical vapor deposition of precursor layers followed by one‐step high‐temperature annealing to synchronously fabricate the front‐side boron emitters and rear‐side TOPCon structures. Benefitting from the excellent passivation and contact properties, the proof‐of‐concept TOPCon devices prepared by such a method deliver a remarkable efficiency of 24.07%.